Environmentally Sustainable Transport in the CEI Countries - Robert Thaler; Peter Wiederkehr (European Journal of Transport and Infrastructure Research, 2004)
Moving people and freight in an environmentally sustainable manner that reduces environmental pollution and health hazards is a key challenge for transport and environment policies in Europe. Present mobility patterns of passenger and freight transport in Central and Eastern Europe do not correspond to the objectives of sustainable development. This paper presents the results of a transport futures study for the CEI region as a whole using backcasting methodology with long-term sustainability criteria to be met by 2030. Achieving environmentally sustainable transport (EST) doesn’t mean less transport and mobility than we have today, but it means primarily maintaining a balanced modal split that results in less environmental and health impacts than it would be under projected future trends. Rail, trams, busses and new forms of flexible inter-modal public transport mobility would have to take a large share and rail transport for passenger and freight as well as inland shipping would have to be nearly doubled by 2030 while road freight could still increase if it is based on alternative fuels reducing its impacts. Technological advancements for passenger cars and lorries, fuels and infrastructure will play an important part to achieve EST, but also ‘smart’ mobility management (e.g. transport avoidance, increasing load factors and modal shift), innovative mobility services and freight logistics would be critical. The implementation of these policies and strategies will require coherent and comprehensive packages of instruments and measures, including: economic instruments, regulatory instruments, changes in infrastructure investment, mobility management, information and education programmes as well as better integration of land use, transport and environment policies. Realising EST will provide new opportunities for businesses to develop and invest in innovative solutions for passenger and freight transport. Overall, achieving EST would constitute a net benefit for the environment and for quality of life in general.